Trends of myopia development among primary and junior school students in the post-COVID-19 epidemic period - Zhou, Wen; Li, Qin; Chen, Hongyan; Liao, Ya; Wang, Wei; Pei, Yifei; Li, Suyan; Zhang, Wenxuan; Wang, Qian; Wang, Xiaojuan (Frontiers in Public Health, 2022)
Purpose: To investigate the trends of myopia among primary and junior school students in the post-COVID-19 epidemic period. Method: A prospective of cross-sectional study using spot photoscreenings in 123,538 children among primary and junior school students from 2019 to 2021 was conducted to evaluate the development of myopia in Xuzhou, China in the post-COVID-19 epidemic period. Equivalent refraction and the prevalence of myopia were recorded. Results: The spherical equivalent refraction of myopia decreased across all grades except grade 1 (0.23±0.56 D in 2019, 0.24±0.63 D in 2020) from 2019 to 2020. However, refraction exhibited a hyperopic shift in 2021 compared to 2020 for grades 1-5 (no significant decreased for grade 4). The prevalence of myopia in all grades increased in 2020 compared to 2019, and the most dramatic changes were observed from grades 2 to 5 and grades 7 to 8 (P<0.05). The changes in myopia prevalence in grades 1-4 were mild, and the reduction in myopia for Grade 5 is significant from 2020 to 2021. Nevertheless, students in grades 6 and 9 exhibited the greatest growth in myopia prevalence (P<0.01). All grades had higher myopia prevalence in 2021 compared with 2019, except grade 1(P=0.25). The prevalence of myopia in girls was higher compared with boys, and the urban myopia prevalence was higher than in rural areas over the three years except in 2019 (P=0.18). Conclusions: The prevalence of myopia increased during the COVID-19 epidemic. However, the spherical equivalent refraction of lower grade children drifted to hyperopia and the trends of myopia development remained stable in the post-COVID-19 epidemic period. We should be more concerned about the prevalence of myopia in graduating for the primary or junior grades in the future.